2017
DOI: 10.1590/1676-0611-bn-2016-0253
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the assemblage of phlebotomine sandflies (Diptera: Psychodidae) along an environmental gradient

Abstract: The geographical distribution of leishmaniasis has undoubtedly expanded, and is now being reported to be in areas that were previously non-endemic. This study therefore aimed to investigate whether there is any variation in the structure and in the composition of phlebotomine communities along an environmental gradient - from a mesic to a xeric environment, across different climatic periods (rainy and dry seasons). Furthermore, we test whether there were differences in sex ratio of sand flies between wet and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…Our results are similar to those obtained in a study conducted in Mali in the same geoclimatic zones where nine sand fly species were identified in the Sahelian zone compared to 13 in the Sudanian zone (34). Similarly, in Brazil, a study of sandfly community composition concluded that species richness, abundance and composition were significantly higher in the wet than in the dry environment (35).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those obtained in a study conducted in Mali in the same geoclimatic zones where nine sand fly species were identified in the Sahelian zone compared to 13 in the Sudanian zone (34). Similarly, in Brazil, a study of sandfly community composition concluded that species richness, abundance and composition were significantly higher in the wet than in the dry environment (35).…”
Section: Discussionsupporting
confidence: 90%
“…Our results are similar to those obtained in a study conducted in Mali in the same geoclimatic zones where nine sand y species were identi ed in the Sahelian zone compared to 13 in the Sudanian zone [34]. Similarly, in Brazil, a study of sand y community composition concluded that species richness, abundance and composition were signi cantly higher in the wet than in the dry environment [35].…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, in some areas, the numbers of cases have increased, and outbreaks have been described in regions where the disease had been considered absent (SALES et al, 2019). This spreading has been related to degradation of natural habitats that may force sandflies to adapt to the modified environment (ANTONINI et al, 2017). This increases the risk of Leishmania transmission in peridomestic and domestic environments.…”
Section: Introductionmentioning
confidence: 99%